Chronic Malnutrition Among Infants of Varanasi - Nanda S; Mishra C.P; Shukla A (Wolters Kluwer Medknow Publications, 1997)
Research question: What is the nutritional status of infants in Varanasi? Objectives: To find out the magnitude of PEM among infants of Varanasi district. Study design: Cross-sectional. Setting: Urban slum and rural areas. Participants: 360 infants. Study variables: Age, height (length), weight. Outcome variables: Protein Energy Malnutrition. Statistical analysis: Simple proportions; Chi- square test. Results: As per the height for age criteria; only 10.56% of infants were stunted (<90% of reference standard) and according to Seoane Latham classification; 44.96%, 6.05% and 4.03% were suffering from acute malnutrition and nutritional dwarfing respectively (90% of reference standard as entry point)